PROCESAMIENTO DE LA INFORMACIÓN FINANCIERA EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL RURAL DE SAN JUAN - Herrera Figueroa, Royer Elier (2019)
The San Juan Rural Parochial Decentralized Autonomous Government is a public institution that works for the benefit of the community and its citizens, and is located in the San Juan parish of the Puebloviejo canton of the province of Los Ríos. This public institution is made up of several departments that fulfill multiple functions, which allow them to participate actively in the transformation of the community and the improvement of the quality of life of its inhabitants. Thus, this public institution plays an important role in this parish, because it is the entity that controls and supervises the works and initiatives for the benefit of this community.